Influence of the Anomalous Patterns of the Mascarene and Australian Highs on Precipitation during the Prerainy Season in South China - Xue Han; Fengying Wei; Xingrong Chen (Advances in Meteorology)
The authors investigate the features of precipitation during the prerainy season in South China (PSCPRS) and the atmospheric circulation in the Southern Hemisphere (SH), which is expected to influence the PSCPRS significantly. The Morlet wavelet method revealed that the PSCPRS has significant interannual variability, especially in its quasi-biennial oscillation. The PSCPRS exhibits a significant monsoonal precipitation pattern. Using singular value decomposition (SVD) and composite analysis, the anomalous characteristics of SH atmospheric circulations and their impacts on the PSCPRS are studied. The results reveal that eastward movements or extensions of the Mascarene high (MH) and Australian high (AH), which have quasi-baroclinic geopotential height structures in the lower and middle troposphere, are the most significant factors affecting the PSCPRS. Their impacts on the PSCPRS anomalies are further studied using the index east of the MH (IEMH) and index east of the AH (IEAH). The IEMH and IEAH have notable significant positive correlations with the PSCPRS. When either the IEMH or IEAH is stronger (weaker), more (less) rainfall occurs during the prerainy season in South China.